Nodular Fasciitis of External Auditory Canal - Ahn, Jihyun (J Pathol Transl Med, 2016)
Nodular fasciitis is a pseudosarcomatous reactive process composed of fibroblasts and myofibroblasts, and it is most common in the upper extremities. Nodular fasciitis of the external auditory canal is rare. To the best of our knowledge, less than 20 cases have been reported to date. We present a case of nodular fasciitis arising in the cartilaginous part of the external auditory canal. A 19-year-old man complained of an auricular mass with pruritus. Computed tomography showed a 1.7 cm sized soft tissue mass in the right external auditory canal, and total excision was performed. Histologic examination revealed spindle or stellate cells proliferation in a fascicular and storiform pattern. Lymphoid cells and erythrocytes were intermixed with tumor cells. The stroma was myxoid to hyalinized with a few microcysts. The tumor cells were immunoreactive for smooth muscle actin, but not for desmin, caldesmon, CD34, S-100, anaplastic lymphoma kinase, and cytokeratin. The patient has been doing well during the 1 year follow-up period.